[Turning on the lights ; Life in Vienna ; The world according to Pidro [videorecording] - Javier, Danny; Lazaro, Cheche; Sucat Thermal Plant (Paranaque). (Quezon City Probe Productions, 1992)
Discusses electricity failure, the national power plants controversy during the Marcos regime under the new administration of the Department of Energy and National Power Corporation. A story on the lives of Filpino nurses in medical centers of Vienna and Australia. Danny Javier a.k.a. Pidro di Montiverdi has personified the new and true Filipino.
Turning on the lights (14 min.) -- Life in Vienna (15 min.) -- The world according to Pidro (10 min.)
VHS.
Keywords: Electric power failure -- Philippines; Filipinos -- Employment. -- Vienna; Impersonation; Male impersonators; Nuclear power plants -- Philippines -- Bataan; Nuclear power plants -- Philippines -- Calaca (Batangas)